The Effectiveness Of The Mobile Driver Test Service Innovation "Si Cemot" On Public Satisfaction (Study At The Transportation Department Of Badung District) - Anak Agung Istri Mas Deny Ernawati (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Conventional motor vehicle periodic test (KIR test) services in many regions still face classic problems. Several studies noted obstacles such as long waiting times, long queues, illegal levies (brokers), and inconsistent officer discipline. The purpose of this study is to determine the level of effectiveness of the "Si Cemot" Mobile KIR test service on public satisfaction in Badung district. The research method used is qualitative with a descriptive qualitative approach. The results or findings of this study are that the Badung district transportation office gets good grades in service quality, and also for facilities are also adequate. However, several obstacles were found in the aspect of service effectiveness from the productivity dimension, several officer respondents noted that the level of utilization of the mobile KIR test service was not optimal. In conclusion, the effectiveness of the "Si Cemot" mobile KIR test service on community satisfaction in Badung district has been running effectively when viewed from the dimensions of service quality and facilities.